Contributions to the ecology of the Benthic macrofauna of the Bot River Estuary - De Decker, Hendrik Paul (Department of Biological Sciences, 2016)
This thesis forms part of a multi-disciplinary study of the Bot River estuary, situated between Kleinmond and Hawston on the southwest coast of the Cape Province, and falls within the framework of the investigation of all Cape estuaries, initiated by SANCOR and co-ordinated by the Estuarine and Coastal Research Unit of the CSIR. The motivation for the research program on the Bot River estuary, in particular, was the need to obtain detailed knowledge of its dynamics in order to be able to address its unique management problems.